Geneses, Sources and Accumulation Process of Natural Gases in the Hinterland of the Junggar Basin - Zhi, Dongming; Wang, Xiaojun; Qin, Zhijun (Frontiers in Earth Science, 2022)
The Junggar Basin is rich in natural gas resources, but it has hardly been explored, with the proven rate being less than 9.0%. Although the hinterland of the Junggar Basin has a favorable condition for natural gas accumulation, the complex gas sources cause great trouble in the selection of zones and belts for exploration. Based on the molecular composition and stable carbon and hydrogen isotope data of 95 natural gas samples from 72 wells in this area, combined with the characteristics of structural evolution history, burial history, hydrocarbon generation and expulsion history, and fluid inclusions, this paper clarified the geneses and sources of natural gas, identified the secondary alteration of natural gas, and restored the process of natural gas accumulation. Natural gas in the hinterland was divided into four types: Type I was oil-type gas from the Lower Permian Fengcheng Formation; Type II was coal-type gas derived from the Carboniferous source rock; Type III was the mixture of Type I and II gases, which constituted the major fraction of natural gases in the hinterland; and Type IV that referred to secondary microbial gas formed by the biodegradation of crude oil. During the Late Cretaceous, the Carboniferous and Fengcheng source rocks entered the gas generation peak and a series of natural gas reservoirs were formed. However, affected by the later tectonic movements, some gas reservoirs were damaged or adjusted, and natural gas leakage and biodegradation occurred. This study has shifted the focus of natural gas exploration in the study area from the petroleum system associated with the Middle Permian source rocks to that with the Lower Permian and Carboniferous source rocks, which is of great significance for natural gas exploration in the Junggar Basin. Further, it provides an example to identify the geneses and sources of natural gas under complex conditions based on integrated geological and geochemical assessments.